Geckos as Springs: Mechanics Explain Across-Species Scaling of Adhesion - Gilman, Casey A.; Imburgia, Michael J.; Bartlett, Michael D.; King, Daniel R.; Crosby, Alfred J.; Irschick, Duncan J. (PLOS ONE, 2015)
One of the central controversies regarding the evolution of adhesion concerns how adhesive force scales as animals change in size, either among or within species. A widely held view is that as animals become larger, the primary mechanism that enables them to climb is increasing pad area. However, prior studies show that much of the variation in maximum adhesive force remains unexplained, even when area is accounted for. We tested the hypothesis that maximum adhesive force among pad-bearing gecko species is not solely dictated by toepad area, but also depends on the ratio of toepad area to gecko adhesive system compliance in the loading direction, where compliance (C) is the change in extension (Δ) relative to a change in force (F) while loading a gecko’s adhesive system (C = dΔ/dF). Geckos are well-known for their ability to climb on a range of vertical and overhanging surfaces, and range in mass from several grams to over 300 grams, yet little is understood of the factors that enable adhesion to scale with body size. We examined the maximum adhesive force of six gecko species that vary in body size ( 2–100 g). We also examined changes between juveniles and adults within a single species (Phelsuma grandis). We found that maximum adhesive force and toepad area increased with increasing gecko size, and that as gecko species become larger, their adhesive systems become significantly less compliant. Additionally, our hypothesis was supported, as the best predictor of maximum adhesive force was not toepad area or compliance alone, but the ratio of toepad area to compliance. We verified this result using a synthetic “model gecko” system comprised of synthetic adhesive pads attached to a glass substrate and a synthetic tendon (mechanical spring) of finite stiffness. Our data indicate that increases in toepad area as geckos become larger cannot fully account for increased adhesive abilities, and decreased compliance must be included to explain the scaling of adhesion in animals with dry adhesion systems.